Synergistic value chain and shared services in oil & gas value chain: the perspective of Petronas – Malaysian Marine Heavy Engineering (MMHE) Ramunia Holdings Berhad. / Mohd Rashidi Muhamad Mustapha, Hazizul Zamrud and Natrah Ismail (Faculty of Business and Management, 2008)
The purpose of this research is to evaluate the strategic and business approach of the recent acquisition of Petronas over Ramunia Holdings Berhad (Ramunia). In January 2008, Petronas had engaged its subsidiary i.e. Malaysia Marine Heavy Engineering Sdn Bhd (MMHE) to initiate a Reverse Take Over on Ramunia. Where Ramunia is offer to purchase MMHE stake with purchase value of RM 3.2 billion, and payments of the purchase shall consider of Ramunia shares issuance that made up of the purchase value to Malaysian International Shipping Corporation (MISC), a Petronas subsidiary that directly hold MMHE stake. Findings reveal that Petronas strategic approach on the acquisition is to ehnanced its value chain in oil and gas business activity. Petronas does not venture into Oil Rigging business activity, which is one of the core chain in a complete oil and gas value chain. In complement of the missing chain and business activity, Petronas interest in Ramunia had paramount when all of Oil Rigging core business activities were ventured by Ramunia. Application on the business research was made by using Porters value chain model together with an intensive review of respective chain business activities in arriving to its common and missing business activities between Petronas, Ramunia and MMHE.